Study the role of c-reactive protein and thrombocytopenia in diagnosing early neonatal sepsis - Babu, N. Aravind (International Journal of Contemporary Pediatrics, 2021)
Background: In clinical practice, early detection of neonatal sepsis remains difficult. Neonatal sepsis diagnosis is a challenge because of its non-specific presentation and the low sensitivity of the time-consuming bacterial cultures. So, many sepsis markers, like C-reactive protein (CRP) and platelet count, are emerging to improve its diagnosis. The aim of the study was to evaluate the role of CRP and platelet count in early neonatal sepsis Methods: This study was conducted in the department of SNCU in Virudhunagar Government Headquarters hospital, 50 neonates with culture-confirmed sepsis were included. Before antibiotic treatment, neonates CRP and platelet count, and other inflammatory markers were assessed. Results: In 50 newborns, culture was positive in 22 cases, CRP was positive in 24 cases, and thrombocytopenia in 18 cases. In 22 culture-positive cases, 19 cases are CRP positive, and 17 cases had thrombocytopenia. In 17 culture-positive thrombocytopenia cases, 16 cases are Gram-negative stain, 1 case is Gram-positive stain. Conclusions: CRP and Platelet can be helpful in the future diagnosis of neonatal sepsis, despite being promising and convenient markers for neonatal sepsis.